Analisis Perawatan Mesin Bubut Menggunakan Metode Reliability Centered Maintenance (RCM) Pada CV. Sumber Jaya Makassar - Laumma, Muhammad Alwi; Yunus, Kartini; Haslinda, Haslinda (JNSTA ADPERTISI JOURNAL, 2024)
The aim of this research is to analyze the determination of the maintenance system and component replacement time intervals using the Reliability Centered Maintenance (RCM) method. This research was carried out at CV. Sumber Jaya Makassar which is located on Jl. Pioneers of Independence, Biringkanaya District, Makassar City. The data obtained shows that there is one lathe machine component that has a very high level of damage, namely the lathe machine electrical system component. From the results of the Mean Time Between Maintenance (MTBM) calculation, it is found that the maintenance interval for the lathe machine electrical system components is every 223.1111 hours, the lathe machine is every 401.6 hours, the lathe machine's fixed head is every 508 hours, the lathe's removable head is every 669.3333 hours. clock and lathe chuck every 1004 hours. To obtain the performance of a lathe that can operate according to its performance, planned or periodic care or maintenance is needed or what is often called preventive maintenance, namely by carrying out daily, weekly and monthly maintenance.